Southeast Kansas Climate Summary for 2023 - Matthew Sittel (Kansas Agricultural Experiment Station Research Reports, 2024)
Temperature and rainfall are important factors influencing agricultural performance. This report summarizes weather conditions in southeast Kansas. Comparisons to long-term records are used to indicate deviations from historical averages. Overall, in 2023 the southeast region had below average precipitation and above normal temperatures.
Keywords: southeast Kansas; precipitation; temperature; long-term climate variability